(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article explores the integration mechanisms of digital and infotainment technologies in the development of tutors’ management activity within higher education institutions. In modern educational environments, tutors are expected to perform complex managerial and pedagogical functions, including student monitoring, academic guidance, coordination, and personalized support. However, traditional approaches to tutor activity often fail to ensure sufficient engagement, responsiveness, and efficiency. The study aims to identify methodological and technological mechanisms through which digital systems and infotainment tools can be integrated into tutor management practices. Based on theoretical and comparative analysis, the article identifies key integration mechanisms such as data-driven monitoring, adaptive communication, interactive support design, digital coordination, engagement-oriented content delivery, and feedback analytics. The findings demonstrate that the integration of digital and infotainment technologies transforms tutor activity into a proactive, student-centered, and analytically informed management system.